Essays on international criminal justice (2012)
Crimes of atrocity have profound and long-lasting effects on any society. The difference between triggering and preventing these tragic crimes often amounts to the choice between national potential preserved or destroyed. It is also important to recognise that they are not inevitable: the commission of these crimes requires a collective effort, an organisational context, and long planning and preparation. Thus, the idea of strengthening preventative action has taken on greater relevance, and is now encompassed in the emerging notion of 'responsibility to prevent'. International courts and tribunals contribute to this effort by ending impunity for past crimes. Focusing investigations and prosecution on the highest leadership maximises the impact of this contribution. The ICC has an additional preventative mandate which is fulfilled by its timely intervention in the form of preliminary examinations. Moreover, when situations of atrocity crimes are triggered, its complementarity regime incentivises states to stop violence and comply with their duties to investigate and prosecute, thus strengthening the rule of law at the national level. The new role granted to victims by the Rome Statute is key to the ICC´s successful fulfilment of these functions. This new book of essays, which includes the author's unpublished inaugural lecture at Utrecht University, examines these issues and places particular emphasis on the additional preventative mandate of the ICC, the ICC complementarity regime, the new role granted to victims, and the prosecution of the highest leadership through the notion of indirect perpetration.